Efficient calculation of the Reed-Muller form by means of the Walsh transform - Porwik, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
The paper describes a spectral method for combinational logic synthesis using the Walsh transform and the Reed-Muller form. A new algorithm is presented that allows us to obtain the mixed polarity Reed-Muller expansion of Boolean functions.
Keywords: Reed-Muller coefficients; Walsh coefficients; coefficient distribution; Boolean function; synthesis of Boolean functions